Effect of Privacy and Safety, Communication, and Physical Environment on Patient Satisfaction and Their Impact on Loyalty (Study at a Dental Clinic in West Jakarta) - Annamaria Gabriela; Pauline H.P. Tan (Budapest International Research and Critics University, 2022)
To determine the effect of privacy and safety, communication, as well as physical environment mediated by patient satisfaction on patient loyalty (Study at a Dental Clinic in West Jakarta). Method: The type of research used is quantitative using the PLS-Structural Equation Modeling (SEM) approach using SMART PLS software. The sample used in this study were 290 dental clinic consumers. Data collection tools in the form of a questionnaire. Result: Privacy and safety, communication, and physical environment have a positive and significant impact on patient satisfaction. Patient satisfaction has a significant and positive effect on customer loyalty. Conclusion: Privacy and safety, communication, and physical environment mediated by patient satisfaction on patient loyalty are all supported hypotheses.